Analisa Pengelompokan Cyber Crime Pada Penerapan Electronic Commerce - Juwita Artanti Kusumaningtyas (Universitas Ngudi Waluyo, 2019)
The rapid development of Information Technology (IT) greatly influences human needs and activities. One influence occurs in buying and selling transactions carried out by two parties, namely consumers and producers or more online. The transaction process is E-commerce (Electronic Commerce). Internet use certainly has risks, one of which is Cyber Crime. Cyber Crime is a crime committed in the internet world involving individuals or groups. Types of Cyber Crime consist of hacking, craking, sniffing and so forth. Cyber Crime cases are grouped into 4 groups namely Interruption, Interception, Modification, and Fabrication. This study uses a literature study method that analyzes 21 journals that discuss Cyber Crime in E-Commerce. The purpose of this study is to determine the Cyber Crime that often occurs in E-Commerce. The results of this study provide recommendations that can be used for developers related to the Cyber Crime group that need to be watched out and prevented.Keywords- E-Commerce, Cyber Crime